From advertising to community: epathetic marketing impact in fast food industry on youth consumer behavior and social connections - S. A. Goryunova (Цифровая социология, 2025)
The results of the sociological study of epathetic fast food advertising impact on consumer behavior and social relations of youth have been considered. The methodological foundations of the study are based on a combined approach, including sociological observation, survey, and questionnaire. Sociological observation makes it possible to determine the real reactions of youth to fast food epathetic marketing, while the survey and questionnaire contribute to the collection of quantitative data on consumer behavior and advertising perception. The analysis of these aspects aims to identify the interrelationships of advertising strategies and youth’s social connections in the digital space, which particularly emphasizes the study’s relevance for understanding contemporary marketing and its impact on youth communities. Based on the empirical study, the authors conclude the interrelationship of fast food epathetic marketing and youth’s consumer behavior by identifying the main positions of key aspects of marketing management techniques. Epathetic advertising of fast food products not only affects the food preferences and habits of youth, but also contributes to strengthening of social ties among the young generation, ensuring their daily communication, exchange of information and emotions, and stimulating daily purchases and consumption of fast food products, considering the opinions of their relatives and acquaintances, which ultimately forms social communities and social capital among the population in Russia.